2013
DOI: 10.1111/hiv.12061
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of HIV screening through the use of rapid tests by general practitioners in a Brussels area with a substantial African community

Abstract: Objectives To assess:1) if HIV screening with rapid tests in neighbourhoods with a substantial African community is feasible and acceptable among GPs and patients; 2) HIV seroprevalence. Methods Multicenter prospective study with 10 trained physicians. Use of HIV standard test and INSTI Ultrarapid test. Inclusion criteria: MSM, sex worker, multiple sexual partners, having returned or coming from a country with high HIV prevalence, IVDU, Indicator conditions as defined by HIV Indicator Diseases across Europe St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 1 publication
0
24
0
1
Order By: Relevance
“…Novel HIV testing technologies were employed by 40 studies in a wide range of clinical settings to increase testing coverage; the majority utilized rapid testing (n = 36) [18,19,22,24,25,34,36,45,46,[48][49][50]56,57,59,65,75,77,81,83,85,88,89,[99][100][101]107,113,117,129,132,134,137,139,141] while four utilized self-sampling (n = 3) [44,52,102] and self-testing strategies (n = 1) [108]. Two of the four self-sampling studies used oral fluid sampling while the self-test required a blood sample.…”
Section: Testing Provision Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Novel HIV testing technologies were employed by 40 studies in a wide range of clinical settings to increase testing coverage; the majority utilized rapid testing (n = 36) [18,19,22,24,25,34,36,45,46,[48][49][50]56,57,59,65,75,77,81,83,85,88,89,[99][100][101]107,113,117,129,132,134,137,139,141] while four utilized self-sampling (n = 3) [44,52,102] and self-testing strategies (n = 1) [108]. Two of the four self-sampling studies used oral fluid sampling while the self-test required a blood sample.…”
Section: Testing Provision Strategiesmentioning
confidence: 99%
“…Two of the four self-sampling studies used oral fluid sampling while the self-test required a blood sample. Novel testing approaches were particularly applied to improve testing coverage in HIV risk groups including MSM (n = 9) [44][45][46]52,57,81,85,129,134], migrants (n = 7) [22,45,46,57,85,129,132], and people who use/inject drugs (PWUD/ PWID) (n = 5) [50,57,85,89,129].…”
Section: Testing Provision Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Results can be read in less than 1 min. Previous studies of the INSTI HIV-1/HIV-2 antibody test found it to be highly sensitive, specific, and easy to use (5)(6)(7)(8)(9)(10)(11). The INSTI Multiplex assay was developed recently, and no published data on its accuracy, feasibility, or acceptability exist yet.…”
mentioning
confidence: 99%